ESTIMATED VALUE AND RENT COST ON CUSTOMER'S DECISION MAKING IN USING GOLD PAWN - Aditya Amanda Pane; Devi Ayu Putri; Sucitra Dewi; Iqbal Nur Hidayat (SEAN Institute, 2023)
This study aims to determine the amount of estimated value and rent costs on customer decision making in using gold pawn products at PT Bank Syariah Indonesia, Tbk. The population in this study were customers who pawned gold at PT Bank Syariah Indonesia, Tbk Medan Branch, namely 355 people. Determination of the number of samples based on Herry King's nomograph with a significance level of 5%, then the number of samples selected was 177 respondents. The analysis technique used in this study is Multiple Linear Regression Analysis. The results of the study show that the estimated value has a positive significant effect on customer decision making in using pawn products. Meanwhile, the rent cost does not have a negative significant effect on customer decision making in using pawn products. Simultaneously, the estimated value and rent costs have a significant effect on customer decision making in using pawn products.